Analytical Methods to Estimate the Thermal Transmittance of LSF Walls: Calculation Procedures Review and Accuracy Comparison - Santos, Paulo (2020)
An accurate evaluation of the thermal transmittance (U-value) of building envelope elements is fundamental for a reliable assessment of their thermal behaviour and energy e ciency. Simplified analytical methods to estimate the U-value of building elements could be very useful to designers. However, the analytical methods applied to lightweight steel framed (LSF) elements have some specific features, being more challenging to use and to obtain a reliable accurate U-value with. In this work, the main analytical methods available in the literature were identified, the calculation procedures were reviewed and their accuracy was evaluated and compared. With this goal, six analytical methods were used to estimate the U-values of 80 di erent LSF wall models. The obtained analytical U-values were compared with those provided by numerical simulations, which were used as reference U-values. The numerical simulations were performed using a 2D steady-state finite element method (FEM)-based software, THERM. The reliability of these numerical models was ensured by comparison with benchmark values and by an experimental validation. All the evaluated analytical methods showed a quite good accuracy performance, the worst accuracy being found in cold frame walls. The best and worst precisions were found in the Modified Zone Method and in the Gorgolewski Method 2, respectively. Very surprisingly, the ISO 6946 Combined Method showed a better average precision than other two methods, which were specifically developed for LSF elements.